ASSOCIATION OF GHRELIN GENE POLYMORPHISMS AND EXPRESSION LEVELS WITH SOME BIOCHEMICAL TRAITS IN BROILER CHICKENS - & et al., Joody (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
This study was conducted to investigate the association of Ghrelin gene polymorphisms and expression levels with some biochemical traits of broiler chickens. Two hundred broiler chicks Ross308, one-day old were wing-tagged and reared under optimal conditions. Blood samples were collected individually from all birds on 21 and 35 days of age. Proventriculus was collected at 35 days of age from thirty birds of each of groups sorted according to growth rate for high, moderate and low to measure ghrelin gene expression by real-time RT-PCR. The serum traits of glucose, uric acid, cholesterol, triglyceride, high density lipoproteins (HDL), low density lipoproteins LDL, total protein, albumin, globulin, aspartate transaminase (AST), alanine transaminase (ALT) and alkaline phosphatase (ALP) were not influenced by ghrelin gene polymorphisms. While   significant (P < 0.01) differences were recorded among the three chicken groups with high, moderate and low ghrelin expression in serum glucose, uric acid, total protein, albumin, cholesterol, triglyceride, HDL, AST, ALT and ALP concentrations at 21 and 35 days of age which increased with increasing ghrelin gene expression. The PCR- RFLP technique revealed no significant differences between GG and LL genotypes of ghrelin gene in all biochemical traits at 21 and 35 days of age, whereas ghrelin gene expression had a significant effect on serum glucose, uric acid, total protein, albumin, cholesterol, triglyceride, HDL, AST,ALT and ALP.